2005
DOI: 10.1097/01.ijg.0000176935.08392.14
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Month, Multicenter, Double-Masked Study of the Safety and Efficacy of Travoprost 0.004%/Timolol 0.5% Ophthalmic Solution Compared to Travoprost 0.004% Ophthalmic Solution and Timolol 0.5% Dosed Concomitantly in Subjects With Open Angle Glaucoma or Ocular Hypertension

Abstract: A fixed combination of travoprost 0.004% and timolol 0.5% produced clinically relevant IOP reductions in patients with open angle glaucoma or ocular hypertension that were comparable to concomitant therapy with its components. Safety and tolerability of the fixed combination were also equivalent to concomitant therapy. Travoprost 0.004%/timolol 0.5% fixed combination offers IOP reduction equivalent to concomitant therapy, with potential benefits that include convenience (fewer bottles and drops per day), impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 34 publications
4
53
0
4
Order By: Relevance
“…Previous studies showed fixed combination of two drugs leads to IOP lowering effects comparable to concomitant use of both components (Hughes et al. 2005; Schuman et al. 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed fixed combination of two drugs leads to IOP lowering effects comparable to concomitant use of both components (Hughes et al. 2005; Schuman et al. 2005).…”
Section: Methodsmentioning
confidence: 99%
“…A further 16 studies were subsequently excluded for various reasons: 4 because the PGA in the Mt was different from that in the FC; one because it was a pooled analysis of already included articles; one because it compared 2 FCs; 2 because they investigated other drugs; one because it had a different aim; 2 because they were not randomized trials; one because it was a comment letter; 3 because the treatment lasted < 4 weeks; and one because it also included patients with normotensive glaucoma (Supplementary Table S2). A total of 17 articles [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] were therefore selected for data extraction and analysis, but as one described the results of 2 studies, 30 the total number of studies was 18. Table 1 shows the characteristics of the 18 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Selection bias could not be excluded in 14 studies 16,18,20,[22][23][24][25][26][27][28][29][30][31] because of the absence of concealed allocation or unclear reporting; however, in the studies where this information was not reported, the double-masked design may have assured concealed allocation. Attrition bias could not be excluded in 6 studies 16,18,[23][24][25]27 in which the analysis was not specified or was not based on the intentionto-treat approach.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…There are evidences that suggest the superiority of fixed combination (Diestelhorst and Larsson, 2004;Schuman et al, 2005). On the other hand, there are adequate evidences to suggest otherwise (Strohmaier et al, 1998;Diestelhorst and Larsson, 2006;Hughes et al, 2005). However, there are many factors such time of IOP measurement, time of instillation, diurnal variation and the possibility of wash out period that are not taken into consideration and lead to over or underestimation (Khouri et al, 2007).…”
Section: Fixed Combinationmentioning
confidence: 99%